Hagenulopsis Ulmer (Ephemeroptera: Leptophlebiidae): re-description, morphological notes and a new species from South America, Brazil - Campos, Rogério; Rodrigues, Jackson A. O.; Lima, Lucas R. C.; Mariano, Rodolfo; Costa, Vinicius; Marulanda, Jhon; Salles, Frederico F. (Zootaxa, 2022)
Hagenulopsis diptera Ulmer, type species of the genus Hagenulopsis, was originally described based on imagos from Santa Catarina State, Southern Brazil. Misconceptions of H. diptera circumscription led to erroneous attribution of material from Minas Gerais and Espírito Santo, Southeastern Brazil, to H. diptera. Despite the increase in the number of species attributed to Hagenulopsis, little attention has been given to the type species. After comparative examination of photographs of the holotype and fresh material of H. diptera from Southeastern Brazil, we conclude that many specimens previously assigned to H. diptera represent a new species. Thus, we redescribe H. diptera and describe a new species Hagenulopsis perere sp. nov. based on eggs, nymphs and imagos. Diagnostic features of Hagenulopsis perere sp. nov. include cross veins between C and RP1 strongly clouded with brown and outer surface of mid femur with a brown spot at midlength. Finally, comments and new records are presented for Hagenulopsis minuta Spieth.